Targeting the Exoskeleton Elementome to Track Tick Geographic Origins - Pacheco, Iván; Acevedo, Pelayo; Prado, Eduardo; Mihalca, Andrei Daniel; de la Fuente, José (Frontiers in Physiology, 2020)
Understanding the origin of ticks is essential for evaluating the risk of tick-borne disease introduction into new territories. However, when collecting engorged ticks from a host, it is virtually impossible to identify the geographical location where this tick was acquired. Recently, the elementome of tick exoskeleton was characterized by using scanning electron microscopy (SEM) and energy dispersive spectroscopy analysis (EDS). The objective of our preliminary proof-of-concept study was to evaluate the use of SEM-EDS for the analysis of tick exoskeleton elementome to gain insight into the tick geographic and host origin. For this preliminary analysis we used 10 samples of engorged ticks (larvae and nymphs of 6 species from 3 genera) collected from various resident hosts and locations. The elementome of the tick exoskeleton was characterized in dorsal and ventral parts with 3 scans on each part using an EDS 80 mm2 detector at 15 kV in a field emission scanning electron microscope. We used principal component analysis (PCA) (varimax rotation) to reduce the redundancy of data under the premise of losing information as little as possible. The PCA was used to test whether the different variables (tick species, stages, hosts or geographic locations) differ in the composition of exoskeleton elementome (C, O, P, Cl and Na). Analyses were carried out using SPSS. The PCA analysis explained a high percentage of variance using the first two factors, C and O (86.13%). The first PC (PC-1; 63.12%) was positively related to P, Cl and Na, and negatively related to C. The second principal component (23.01%) was mainly positively related to C. In the space defined by the two extracted PC (PC-1 and PC-2), the elementome of tick samples was clearly associated with tick species, but not with developmental stages, hosts or geographic locations. A differentiated elementome pattern was observed within Romanian regions (CJ and TL) for the same tick species. The use of the SEM-EDS methodological approach provided additional information about the tick exoskeleton elementome with possible applications to the identification of tick origin host and location.